The Patriotic Turn in Russia: Political Convergence of the Russian Orthodox Church and the State? - Shakhanova, Gaziza (Politics and religion, 2022)
Following two decades of a state-supported patriotic campaign, the Russian Orthodox Church has dramatically increased its presence in the public sphere: in the Armed Forces, in public schools and universities, and even in retirement houses and prisons. The Church's recent activities seem to have no territorial limits: they reach up to the space station "Mir" and the Russian Antarctic Station, as well as the (Russian) Orthodox believers in 62 states. Using a critical discourse analysis of the speeches of top Church leaders as our main methodological tool, our research explores the Church's policies on patriotism and patriotic education, its re-interpretation of historical memory, and the role of the Church in Russian politics. We try to show that while the Church's agenda and approach to politics are idiosyncratic, the Church has become a key actor with an increasingly important political role.